Heterologous expression and functional characterization of Drosophila suzukii OR69a transcript variants unveiled response to kairomones and to a candidate pheromone. - Cattaneo, A.M.; Witzgall, P.; Kwadha, C.A.; Becher, P.G.; Walker, W.B. (Journal of pest science, 2023)
Drosophila suzukii is a main pest of berries on all continents. Population control relies on insecticides and a current research challenge is to develop alternative strategies. Methods based on behavior-modifying semiochemicals are widely used against other horticultural insects, and the functional characterization of chemoreceptors facilitates the identification of active compounds. Following heterologous expression of single olfactory receptors (ORs) in ab3A olfactory sensory neurons of D. melanogaster, we screened three transcript variants from the OR69a-locus (DsuzOR69aA, DsuzOR69aB, DsuzOR69aC), demonstrating binding to two possible kairomones (3-octanol and R-carvone) and to a possible fly-emitted volatile compound [(Z)-4-nonenal], although with different pharmacological qualities. By coupling Gas Chromatography to SSR (GC-SSR), these ligands enhanced ab3A-spiking at nanogram-aliquots in a complementary fashion among the different OR69a-variants, and we identified another possible kairomone, methyl salicylate, as the most active and specific ligand for the sole DsuzOR69aB. In testing headspaces collected from D. suzukii females and from the fly-associated yeast Hanseniaspora uvarum we did not observe activation from female headspaces but activation from yeast headspaces. In situ hybridization analysis on D. suzukii antennae suggests unique expression of OR69a-subunits in specific neurons, and points toward co-expression within the same neurons. The OR69a-subunits of D. suzukii constitute cation channels, which binding suggests kairomone specificity, even if effects coexist for a complementary binding of (Z)-4-nonenal. Methyl salicylate is the most active ligand and is specific to the sole DsuzOR69aB, inspiring future investigation to validate potentials of this compound for D. suzukii control strategies.